Hepatic lipid peroxidation in vivo in rats with chronic iron overload. - Bacon, B R (1983)
Peroxidative decomposition of cellular membrane lipids is a postulated mechanism of hepatocellular injury in parenchymal iron overload. In the present study, we looked for direct evidence of lipid peroxidation in vivo (as measured by lipid-conjugated diene formation in hepatic organelle membranes) from rats with experimental chronic iron overload. Both parenteral ferric nitrilotriacetate (FeNTA) administration and dietary supplementation with carbonyl iron were used to produce chronic iron overload. Biochemical and histologic evaluation of liver tissue confirmed moderate increases in hepatic storage iron. FeNTA administration produced excessive iron deposition throughout the hepatic lobule in both hepatocytes and Kupffer cells, whereas dietary carbonyl iron supplementation produced greater hepatic iron overload in a periportal distribution with iron deposition predominantly in hepatocytes. Evidence for mitochondrial lipid peroxidation in vivo was demonstrated at all three mean hepatic iron concentrations studied (1,197, 3,231, and 4,216 micrograms Fe/g) in both models of experimental chronic iron overload. In contrast, increased conjugated diene formation was detected in microsomal lipids only at the higher liver iron concentration (4,161 micrograms Fe/g) achieved by dietary carbonyl iron supplementation. When iron as either FeNTA or ferritin was added in vitro to normal liver homogenates before lipid extraction, no conjugated diene formation was observed. We conclude that the presence of conjugated dienes in the subcellular fractions of rat liver provide direct evidence of iron-induced hepatic mitochondrial and microsomal lipid peroxidation in vivo in two models of experimental chronic iron overload.